Potential of Freshwater Fisheries as a Supporting Factor for Minawisata of Tasikmalaya - Elgar Balasa Singkawijaya; Siti Fadjarajani; Amar Tiwi Nurohmah (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2019)
Cibunigeulis Village, Bungursari District, Tasikmalaya has a huge the potential for freshwater fishery cultivation and minawisata activities. The research objective is to determine the characteristics of the freshwater fisheries sector as a supporting capacity for minawisata activities. The method used in this research is quantitative descriptive method. The results showed the cultivation of fisheries activities have a carrying capacity of ideal nurseries such as ponds, labor, breeding, knowledge and capital. The stages to have a good cultivation are the preparation stage of the pond, fertilizing, spawning, and hatching stage of the eggs become fish larva. The next stages, are the magnification stage, the harvesting stage, the processing stage and marketing stage. If these stages can be managed well it will also produce a good product. The fish are the primary commodity for consumption needs both inside the city and outside the city. Some fish products include, carp, catfish, Nile tilapia fish, tilapia, silver catfish and other fish. in terms of Minawisata activities, the village can be developed for fishing activities, culinary and fisheries exhibitions